Spatial consequences of urban densification policy: Floor-to-area ratio policy in Tehran, Iran - Ghadami, M.; Newman, Peter (2018)
The purpose of this paper is to investigate the effect of the urban densification policies made after the Islamic Revolution on the urban spatial structure of Tehran as the most important metropolis in Iran. The Hot Spot approach based on the Getis Ord Local G statistical test and Arc GIS 10.2 software was employed in this study. The advantage of the Geo-statistic technique used in this study is that this model does not require the exact location of the city centre to map and determine its spatial structure. The results show that the spatial structure of Tehran was affected by the non-spatial densification policies for 30 years (until Tehran’s Master Plan in 2007). Furthermore, these policies were greatly dependent on the financial benefits from the sale of the FAR permission and fines related to the ignorance of the lawful regulations. There is a spatial imbalance between the population and activity distribution patterns in the structure of Tehran. However, the negative spatial consequences of the densification policies are declining capacity of the city centre and the inner wards in retaining the population, and growing population density in the northern outer wards of Tehran.